Pengaruh Financial Knowledge terhadap Keputusan Keuangan Usaha Kecil dan Menengah (UKM) di Pulau Lombok dengan Risk Perception sebagai Variabel Intervening - Hidayati, Siti Aisyah; Wahyulina, Sri; Suryani, Embun (Universitas Mataram, 2024)
This study aims to analyze the impact of Financial Knowledge on Financial Decision-Making, with Risk Perception as an intervening variable among Small and Medium Enterprise (SME) owners in Lombok Island. The research adopts a quantitative approach with explanatory research design. The population includes all SMEs in Lombok, with a sample of 35 SMEs involved in the pottery craft industry that have engaged in export activities, selected using judgment sampling. The respondents are the owners of these SMEs, who participated through questionnaires. Data were analyzed using Generalized Structured Component Analysis (GSCA). The findings reveal that Risk Perception does not mediate the relationship between Financial Knowledge and Financial Decision-Making. However, Financial Knowledge has a significant negative effect on Risk Perception, and Risk Perception has a significant negative effect on Financial Decision-Making. These results are influenced by the characteristics of the respondents, who are mostly in their productive age, predominantly male, with education levels ranging from high school to university, and have been in business for over 15 years